HUBUNGAN KECERDASAN SPIRITUAL DENGAN PERILAKU MENYIMPANG - Mulyati, Sri; Hamidah, Nur; Bassar, Agus Samsul (Prodi PAI IAILM Suryalaya, 2022)
This study aims to determine the relationship between students' spiritual intelligence and awareness of avoiding deviant behavior in Serba Bakti Suryalaya Islamic Junior High School students. The method used in this study is a descriptive method with a quantitative approach, namely a research method that is shown to describe existing phenomena, currently taking place, or in the past. The results of this study indicate that the relationship between spiritual intelligence and deviant behavior in students of SMP Islam Serba Bakti Suryalaya there is a significant positive correlation with the result of